Assessing changes in range of motion in adolescent patients undergoing myoActivation® for chronic pain related to myofascial dysfunction: a feasibility study - Bhatnagar, Tim; Azim, Farah T.; Behrouzian, Mona; Davies, Karen; Wickenheiser, Diane; Jahren, Gail; West, Nicholas; Leveille, Lise; Lauder, Gillian R. (Frontiers in Pain Research, 2023)
Introduction myoActivation® assessment utilizes systemized movement tests to assess for pain and limitations in motion secondary to myofascial dysfunction. myoActivation needling therapy resolves the myofascial components of pain and is associated with immediately observed changes in pain, flexibility, and range of motion. The principal aim of this feasibility study was to objectively characterize the kinematic metrics of upper and lower body motion before and after myoActivation movement tests and therapy. Methods Five consecutive eligible adolescent participants considered appropriate for myoActivation were consented to receive their myoActivation intervention in a motion laboratory. Clinical motion analysis was used to measure the changes in maximum range of motion (maxROM) and maximum angular speed to maximum ROM (speedROM) of movement tests predicted to change. Metrics were analyzed to assess changes over specified time intervals - i) baseline to after initial myoActivation session, and ii) baseline to after complete myoActivation course. Each participant served as their own control. Results We demonstrated objective evidence of improved maxROM and/or speedROM in 63% of the movement tests predicted to change after just one session of myoActivation and in 77% of movement tests predicted to change over the complete course of treatment. The myoActivation clinician observed positive change in 11/19 of movement tests across all patients, that were predicted to change after the initial myoActivation session; 81% of these positive changes were confirmed by the kinematic data. Discussion Clinical motion analysis provides objective support to clinicians evaluating, treating, and teaching myofascial release. A larger, prospective clinical trial is warranted to explore the impact of myoActivation on movement. Refinement of observation techniques and outcome measures established in this feasibility study will strengthen future clinical motion analysis of the myoActivation process.